Clinicopathological value and underlying molecular mechanism of annexin A2 in 992 cases of thyroid carcinoma. (June 2020) - Qin, Yong-ying; Huang, Su-ning; Chen, Gang; Pang, Yu-yan; Li, Xiao-jiao; Xing, Wen-wen; Wei, Dan-ming; He, Yun; Rong, Min-hua; Tang, Xiao-zhun
Graphical abstract: Highlights: Significant upregulation of ANXA2 expression is evidenced in thyroid carcinoma by multiple detecting approaches. Upregulated ANXA2 is strongly related to the development of thyroid carcinoma. ANXA2 coexpressed genes are mostly enriched in the pathway of extracellular matrix-receptor interaction. ANXA2 is a target of miR-23b-3p in thyroid carcinoma. Abstract: Background: Thyroid carcinoma (THCA) is one of the most frequent endocrine cancers and has increasing morbidity. Annexin A2 (ANXA2) has been found to be highly expressed in various cancers; however, its expression level and potential mechanism in THCA remain unknown. This study investigated the clinicopathological value and primary molecular machinery of ANXA2 in THCA. Material and Methods: Public RNA-sequencing and microarray data were obtained and analyzed with ANXA2 expression in THCA and corresponding non-cancerous thyroid tissue. A Pearson correlation coefficient calculation was used for the acquisition of ANXA2 coexpressed genes, while edgR, limma, and Robust Rank Aggregation were employed for differentially expressed gene (DEG) in THCA. The probable mechanism of ANXA2 in THCA was predicted by gene ontology and pathway enrichment. A dual-luciferase reporter assay was employed to confirm the targeting relationships between ANXA2 and its predicted microRNA (miRNA). Results: Expression of ANXA2 was significantly upregulated in THCA tissues with a summarized standardized mean difference of 1.09 (P < 0.0001) based on 992 THCA cases and 589 cases of normal thyroid tissue. Expression of ANXA2 was related to pathologic stage. Subsequently, 1442 genes were obtained when overlapping 4542 ANXA2 coexpressed genes with 2248 DEGs in THCA; these genes were mostly enriched in pathways of extracellular matrix-receptor interaction, cell adhesion molecules, and complement and coagulation cascades. MiR-23b-3p was confirmed to target ANXA2 by dual-luciferase reporter assay. Conclusions: Upregulated expression of ANXA2 may promote the malignant biological behavior of THCA by affecting the involving pathways or being targeted by miR-23b-3p.